Элементы современной математической физики учебное пособие для вузов - Багров В. Г. Владислав Гаврилович; Белов В. В. Владимир Владимирович; Задорожный В. Н. Валерий Николаевич; Трифонов А. Ю. Андрей Юрьевич (Томск, Изд-во ТПУ, 2012)
На англ. яз.